Darboux problem for fractional partial hyperbolic differential inclusions on unbounded domains with delay - HELAL, Mohamed (Studia Universitatis Babeș-Bolyai Mathematica, 2022)
In this paper we investigate the existence of solutions of initial value problems (IVP for short), for partial hyperbolic functional and neutral differential inclusions of fractional order involving Caputo fractional derivative with finite delay by using the nonlinear alternative of Frigon type for multivalued admissible contraction in Fr´echet spaces. Mathematics Subject Classification (2010): 26A33, 34K30, 34K37, 35R11. Received 12 December 2019; Accepted 17 January 2020.